Quality assurance in geriatrics - Opportunities and risks involved in the current health care reform in Germany - Sieber, Cornel; Troegner, J.; Penz, M.; Gerber, H. (Rehabilitation (Germany), 2008)
Geriatrics is needed as an independent discipline to cope with the demographic challenges ahead in a medically qualified manner. Geriatrics is a "supraspeciality" and not a "subspeciality" of Internal Medicine, because geriatrics typically combines the different medical disciplines and does not play a role as an independent functional area. For general practitioners and medical specialists a geriatric qualification is required. The geriatric structures in place in the German federal states need to be adapted and advanced with a focus on ambulatory geriatric service provision. The current health care reform has resulted in a strengthening of rehabilitation in general and in particular of an ambulant/mobile service approach. The resultant opportunities and risks are described. Internal and external quality assurance is indispensable for the advancement of structures including geriatrics and social medicine.
Keywords: geriatrics; quality assurance; current health care reform